2021
DOI: 10.3389/fnagi.2021.617370
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Peripheral Immune Activation in Parkinson’s Disease

Abstract: BackgroundAccumulating evidence has revealed that peripheral immunity is involved in Parkinson’s disease (PD). However, the results regarding the percentage of T-cell subsets are inconsistent, and the changes of immunoglobins levels have been seldom studied in PD patients.MethodsSerum levels of the percentage of T-cell subsets and immunoglobulins were measured in 761 PD patients and 761 age- and gender-matched healthy controls. The correlations between the variables of peripheral immune activation (PIA) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…A meta-analysis including 21 case-control studies and 943 PD patients confirmed that the numbers of CD3 + and CD4 + T cells were significantly decreased in PD [23]. In contrast with these results, another study found that PD patients had an increase in the percentage of CD3 + and CD4 + T s and the CD4 + /CD8 + ratio [24], whereas other groups did not find any significant difference in the percentage of both CD4 + and CD8 + between PD patients and controls [17,18,25]. Undoubtedly, the composition of peripheral T cells from PD patients in the reported studies was quite heterogeneous, which could be explained by the influence of ethnic variations or other relevant disease-related confounders.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 96%
“…A meta-analysis including 21 case-control studies and 943 PD patients confirmed that the numbers of CD3 + and CD4 + T cells were significantly decreased in PD [23]. In contrast with these results, another study found that PD patients had an increase in the percentage of CD3 + and CD4 + T s and the CD4 + /CD8 + ratio [24], whereas other groups did not find any significant difference in the percentage of both CD4 + and CD8 + between PD patients and controls [17,18,25]. Undoubtedly, the composition of peripheral T cells from PD patients in the reported studies was quite heterogeneous, which could be explained by the influence of ethnic variations or other relevant disease-related confounders.…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 96%
“…In 2021, we compared 761 age–gender matched healthy controls with 761 PD patients and found that the ratio of CD4/CD8 in PD patients was higher than that in healthy controls, and the percentage of CD4+ T cells was negatively correlated with the Hoehn and Yahr (H&Y) stage [ 145 ]. However, we did not compare the subtypes of CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the inflammatory progress of CNS, peripheral myeloid cells (such as monocytes) can be recruited into the brain through disturbed BBB and further participate in the inflammatory processes ( 27 ). Peripheral immune activation is enhanced in PD patients, and dynamic changes in the percentage of CD4+ T cells and IgG level suggest that peripheral immunity plays a positive role in initiation or exacerbation of neurodegeneration ( 30 ). The autoantibodies against α-synuclein were related to disease status in the serum and cerebrospinal fluid of PD patients ( 31 ); furthermore, a study confirmed that the repertoire of high-affinity anti-α-synuclein autoantibodies was significantly reduced in prodromal phases of PD ( 32 ), which indicates that impaired reactivity towards α-synuclein occurs prior to disease onset and humoral immune response is involved in the pathophysiology of neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%